PERANCANGAN SMART PARKING SYSTEM BERBASIS ARDUINO UNO - Andri Firmansyah; Dimas Ardi Pratama (Teknik Informatika, Universitas Pelita Bangsa, 2018)
In Indonesia, it is very rarely discussed about Smart Parking technology, especially special areas such as multi-storey buildings such as shopping centers, hospitals, airports, schools, and offices. One of the technological developments in the field of transportation that we can find is the parking service system. To design a circuit that functions to foster a parking system. To see for sure, a filled and unfilled parking area. This study uses a Smart Parking System based on Arduino Uno and is made at Rama Futsal with the address of Perum Wisma Jaya, Jl. Kusuma Barat No.1, Duren Jaya, Bekasi Timur, RT.007 / RW.017, Duren Jaya, Kec. Bekasi Tim., Bekasi City, West Java 17111. Parking areas are not subject to ultrasonic sensors to control using the Arduino Uno. Keywords : Arduino Uno, Control System, Smart Parking, Ultrasonic Sensor.